Transformasi Sistem Pemanenan Latex Tanaman Karet: Review - Junaidi Junaidi (JURNAL BUDIDAYA PERTANIAN, 2020)
Most people understate that latex harvesting is merely cutting the bark and collecting the sap. Since it was cultivated in the monoculture plantation system, rubber (Hevea brasiliensis) harvesting system has been transformed continually. This article presents the transformation of rubber harvesting systems, tapping innovations that have been developed, and the current condition of rubber agribusiness and its impact on the tapping system applied. At the beginning of the development of the rubber cultivation era, tapping was conducted with multiple slicings to gain high rubber yield. This system turned into one slice to extend the economic span of the plant. The invention of latex stimulants transformed the rubber tapping system from once every two days (d2) without stimulants to once every three days (d3) with stimulants. In the case of the tapping technique, several tapping systems have been developed, including puncture tapping, upward and double-cut tapping, Alternate Tapping System, and Change Over Panel. Except for the puncture tapping, those tapping systems are still used nowadays. Latex diagnosis, that is the measurements of the sucrose, inorganic phosphate, and thiol contents in the latex, became the basis of clonal grouping and the clonal typology tapping system. The current low rubber price renders the adoption of low-frequency tapping systems (d4, d5, or d6) with high dose and frequency of stimulant application. In the future, the low-frequency tapping system will remain the ultimate choice as labor costs continue rising. Besides, the use of sensory technology and digital instruments is being widely studied, which indicates that the latex harvesting system in rubber plants is believed to continue to develop. Keywords: Hevea brasiliensis, latex diagnosis, latex yield, stimulant, tapping ABSTRAK Sebagian besar masyarakat beranggapan bahwa memanen lateks hanya mengiris kulit dan menampung getahnya. Namun sebenarnya, sejak dikembangkan dalam sistem perkebunan monokultur, sistem pemanenan lateks karet (Hevea brasiliensis) terus mengalami pembaharuan. Artikel ini menyajikan transformasi sistem pemanenan lateks tanaman karet, inovasi-inovasi yang pernah dikembangkan, serta kondisi agribisnis karet saat ini dan dampaknya terhadap sistem sadap yang diterapkan. Pada awal perkembangan perkebunan karet, penyadapan dilakukan dengan banyak irisan untuk mendapatkan hasil sebanyak-banyaknya. Ini kemudian berubah menjadi satu irisan untuk memperpanjang umur ekonomis tanaman. Penggunaan stimulan mengubah sistem penyadapan karet dari dua hari sekali (d2) tanpa stimulan menjadi tiga hari sekali (d3) dengan stimulan. Dalam hal teknis, beberapa sistem sadap pernah dikembangkan antara lain, sadap tusuk, penyadapan ke arah atas, sadap ganda, Alternate Tapping System, dan Change Over Panel. Selain sadap tusuk, inovasi-inovasi penyadapan tersebut tetap digunakan sampai saat ini. Diagnosis lateks melalui pengukuran kadar sukrosa, fosfat anorganik, dan thiol dalam lateks, menjadi dasar pengelompokan klon dan penyadapan tipologi klonal. Harga karet yang rendah saat ini menyebabkan perusahaan perkebunan cenderung mengadopsi sistem sadap frekuensi rendah (d4, d5, atau d6) dengan dosis dan frekuensi stimulan yang tinggi. Di masa yang akan datang, sistem sadap frekuensi rendah akan tetap menjadi pilihan utama karena upah tenaga kerja terus meningkat. Selain itu, penggunaan teknologi sensorik dan instrumen digital mulai banyak diteliti. Melihat fakta-fakta ini, sistem pemanenan lateks pada tanaman karet diyakini akan terus berkembang. Kata kunci: diagnosis lateks, Hevea brasiliensis, penyadapan, produksi karet, stimulan